The effort and intricacies of generating experience-near language - David Newman (International Journal of Narrative Therapy and Community Work)
In this paper I explore Clifford Geertz’s distinction between experience-near and experience- distant language. In the process, I draw from mad studies and mental health service user epistemology, both written and generated through my work. I also draw on the work of the historian of emotion Tiffany Watt Smith. Three specific practices in relation to language use are proposed: how we can invigorate the agency or meaning-making in language use; how we can use language to assist people to become familiar with, not alienated from, their experience; and how we might name and question the values or obligations that get smuggled in with emotion talk. I also provide three exercises to explore these themes.